2021
DOI: 10.1002/advs.202102756
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Fabrication of Metallic Nanogaps at the Sub‐10 nm Level

Abstract: Metallic nanogaps with metal-metal separations of less than 10 nm have many applications in nanoscale photonics and electronics. However, their fabrication remains a considerable challenge, especially for applications that require patterning of nanoscale features over macroscopic length-scales. Here, some of the most promising techniques for nanogap fabrication are evaluated, covering established technologies such as photolithography, electron-beam lithography (EBL), and focused ion beam (FIB) milling, plus a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 165 publications
(330 reference statements)
0
33
0
Order By: Relevance
“…As predicted by Moore’s Law, the density of integrated circuits (ICs) has been improved exponentially for high-performance semiconductor devices 1 and the photolithographic fabrication of nanoscale semiconductor devices requires increasingly high-resolution techniques. 2 , 3 Extreme ultraviolet lithography (EUVL) and electron beam lithography (EBL) are key advanced lithographic technologies for the production of feature sizes lower than 20 nm. 4 10 As the feature size decreases, the requirements for resists’ performance have gradually increased.…”
Section: Introductionmentioning
confidence: 99%
“…As predicted by Moore’s Law, the density of integrated circuits (ICs) has been improved exponentially for high-performance semiconductor devices 1 and the photolithographic fabrication of nanoscale semiconductor devices requires increasingly high-resolution techniques. 2 , 3 Extreme ultraviolet lithography (EUVL) and electron beam lithography (EBL) are key advanced lithographic technologies for the production of feature sizes lower than 20 nm. 4 10 As the feature size decreases, the requirements for resists’ performance have gradually increased.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, metal nanostructures arrays have been widely used for bioelectronics because of the special advantages in localized surface plasmon resonance. [140][141][142] On this basis, Shen et al proposed a controlled method to synthesize Au NRs and weld them together, as shown in Figure 8c. [143] After synthesizing Au NRs through the seed-mediated growth method, DNA origami was introduced as a template to arrange the anisotropic Au NRs into tip-to-tip dimer structures (Figure 8d).…”
Section: Template-assisted Self-assemblymentioning
confidence: 99%
“…Various nanofabrication methods, such as electron-beam lithography (EBL), extreme-ultraviolet lithography (EUVL), focused-ion beam (FIB) milling, breaking and cracking methods, capillary force-assisted (CFA) lithography, , and block copolymer lithography , have been used to pattern ordered metallic arrays with SERS-active nanostructured motifs. However, EBL, EUVL, and FIB methods are too costly and time-consuming for fabricating dense nanostructure arrays over wide areas.…”
Section: Introductionmentioning
confidence: 99%